Classification of the Bazhenov Formation Using Well Logs (R Field) - Simonov D. A. Dmitry Arturovich; Baranov V. E. Vitaliy Evgenievich; Bukhanov N. V. Nikita Vladimirovich; Beschasova P. A. Polina Anatoljevna (Exploration & Production in Unconventional Reservoirs, 2016)
Title screen